Estudo de utilização de medicamentos e fatores associados à polifarmácia em pacientes portadores de Diabetes Mellitus em municípios de Minas Gerais - Michael Ruberson Ribeiro da Silva (2015)
Diabetes Mellitus (DM) is a worldwide epidemic, it is a major challenge for health systems in the world. It is a chronic disease of multiple etiology, due to the lack and/or the inability of insulin to properly exert its effects. Recent studies in different populations of patients with DM reported the use of a large number of drugs, leading these patients to the practice of polypharmacy. However, no studies have been observed the association of polypharmacy its associated factors. In this sense, the aim of the study was to evaluate the profile of drug use and factors associated with polypharmacy in patients with diabetes mellitus (DM) in Minas Gerais, Brazil. A cross-sectional study was performed in 63 municipalities of Minas Gerais in January and February 2014. A descriptive analysis was used for the characteristics of respondents and medicines in use by the Anatomical-Therapeutic-Chemical encoding. The association between socio-demographic and clinical characteristics with polypharmacy was observed by means of logistic regression. 2619 people with DM were interviewed, most had 60 years or more and were female, and 83.7% with type 2 DM and 10.4% with type 1 DM. Polypharmacy was observed in 56.5% of participants. The most frequent therapeutic classes were drugs for DM, agents on the renin-angiotensin system and diuretics. Age over 40 years, bad or very bad self-reported health, presence of five or more comorbidities, diagnostic time above 10 years, have consulted the physician four times or more in the last year, lack of regular physical activity, interruption of usual activities during the last 15 days and have private health insurance were factors associated with polypharmacy. Most participants had polypharmacy, which increases the risk of adverse reactions and drug interactions. Factors such as age, comorbidities and access to health services contributed to increased use of medication. Therefore, there is need for trained professionals to provide proper care, improve the quality of medication and minimize the negative consequences on the health of this population.